gyrA Mutations Associated with Quinolone Resistance in Bacteroides fragilis Group Strains - Oh, Herin (American Society for Microbiology, 2001)
Mutations in the gyrA gene contribute considerably to quinolone resistance in Escherichia coli. Mechanisms for quinolone resistance in anaerobic bacteria are less well studied. The Bacteroides fragilis group are the anaerobic organisms most frequently isolated from patients with bacteremia and intraabdominal infections. Forty-four clinafloxacin-resistant and-susceptible fecal and clinical isolates of the B. fragilis group (eight Bacteroides fragilis, three Bacteroides ovatus, five Bacteroides thetaiotaomicron, six Bacteroides uniformis, and 22 Bacteroides vulgatus) and six ATCC strains of the B. fragilis group were analyzed as follows: (i) determination of susceptibility to ciprofloxacin, levofloxacin, moxifloxacin, and clinafloxacin by the agar dilution method and (ii) sequencing of the gyrA quinolone resistance-determining region (QRDR) located between amino acid residues equivalent to Ala-67 through Gln-106 in E. coli. Amino acid substitutions were found at hotspots at positions 82 (n = 15) and 86 (n = 8). Strains with Ser82Leu substitutions (n = 13) were highly resistant to all quinolones tested. Mutations in other positions of gyrA were also frequently found in quinolone-resistant and -susceptible isolates. Eight clinical strains that lacked mutations in their QRDR were susceptible to at least two of the quinolones tested. Although newer quinolones have good antimicrobial activity against the B. fragilis group, quinolone resistance in B. fragilis strains can be readily selected in vivo. Mutational events in the QRDR of gyrA seem to contribute to quinolone resistance in Bacteroides species.